Research on the use of 3D modeling and motion capture technologies for making sports training easier - Muhammad Talha (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The essential purpose of this research study is to measure the study on the use of 3D modeling and motion capture technologies for making sports training easier. This research study was conducted in china for determines whether the research study used specific MCQs-based questions related to the research topic included and its variables. 3D modeling is an independent variable, and motion capture technologies are the independent variable for determining the sport training effects and how it’s easier. This research study depends upon it became. To determine the research study used analytical software of smart PLS and generated specific results, including the smart PLS Algorithm model, segmentation analysis, indicator correlation, and significant analysis. This research study describes the econometric model between dependent and independent variables. A comprehensive research study found that there is a positive effect of 3d modeling and motion capture technologies on sports training. This quality feedback is very good for encouraging the players to play good sports. In the sports field, one major problem regarding the result and timing of various sports has been solved using electronic technology timers. These electronic timers automatically calculate the timing of an athlete during a sport, and the data then provides help in predicting the winner of any sport.